2005
DOI: 10.1002/pca.805
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of the major saponin mixture bacoside A in Bacopa monnieri by HPLC

Abstract: Bacoside A, the putative bioactive component of the Indian medicinal plant Bacopa monnieri, was found to be a mixture of saponins with bacoside A3 (1), bacopaside II (2), jujubogenin isomer of bacopasaponin C (3) and bacopasaponin C (4) as major constituents. An HPLC method together with an optimised extraction procedure was developed for the estimation of 1-4 in B. monnieri to enable standardisation of the latter. Concentration ranges of the analytes in samples of B. monnieri collected from different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 18 publications
0
79
0
Order By: Relevance
“…28 Chemical characterizations of the plant have been carried out by many investigators. [29][30][31][32][33][34][35][36][37][38][39][40] There are no data currently available on the pharmacokinetics of Bacopa or its saponins. Phase I clinical studies confirmed the safety of bacosides in healthy male volunteers at both single and chronic dosing administered over a period of 4 weeks 7 and 6 weeks with a dose of up to 450 mg of dried water extract.…”
mentioning
confidence: 99%
“…28 Chemical characterizations of the plant have been carried out by many investigators. [29][30][31][32][33][34][35][36][37][38][39][40] There are no data currently available on the pharmacokinetics of Bacopa or its saponins. Phase I clinical studies confirmed the safety of bacosides in healthy male volunteers at both single and chronic dosing administered over a period of 4 weeks 7 and 6 weeks with a dose of up to 450 mg of dried water extract.…”
mentioning
confidence: 99%
“…Ganzera et al 15) reported the method for quantification of six saponins using gradient HPLC with PDA detector, but one of the major peaks was not completely characterized. Deepak et al 16) determined bacoside A which contains 4 compounds by HPLC, but did not consider bacoside B. In another report, bacosides were estimated by HPLC, coupled NMR, MS and bioassay methods described.…”
mentioning
confidence: 99%
“…A high performance thin-layer chromatographic (HPTLC) 11) method was developed for the estimation of bacoside A in Bacopa monnieri plant and its formulations. A few high performance liquid chromatographic (HPLC) [12][13][14][15][16] methods were also developed for the quantification of bacosides in Bacopa monnieri extracts and formulations. Ganzera et al 15) reported the method for quantification of six saponins using gradient HPLC with PDA detector, but one of the major peaks was not completely characterized.…”
mentioning
confidence: 99%
“…Two common flavonoids, luteolin and apigenin, were also presented (Deepak et al, 2005). Our HPLC analysis showed that the bacoside A contained in B. monniera extract was approximately 0.6% (w/w), which was in the same range as reported previously (Deepak et al, 2005).…”
Section: Phagocytic Activity Assaysmentioning
confidence: 50%